PENGEMBANGAN MEDIA PEMBELAJARAN MENGGAMBAR ORNAMEN DESAIN HENNA BERBASIS AUGMENTED REALITY - Balise, Hasniyati; Syahrir, Nurlina; Alimuddin, Alimuddin (Nuansa Journal of Arts and Design, 2024)
Research and development of augmented reality-based learning media that can visualize decorative/ornament materials can make it easier for students to understand the material. The type of research used is research and development (Research and Development), using the ADDIE development model (Analyze, Design, Development, Implementation and evaluation) which is limited to the formative evaluation stage due to time constraints. The products that have been developed are then validated by experts, namely material experts, media experts, and users. After going through the validation stage and also revision, it was then field tested to find out the response of students and the effective trial of drawing augmented reality-based henna design ornaments on Class VII students of UNISMUH Makassar Junior High School. The results of research and development that have been carried out obtained (1) the average score of the material expert validation score of 4.72 (2) The average score value of media expert validation is 4.8 These results indicate that the validity level of the learning media developed is declared very valid (1) Practicality Test with an average user validation score of 5 very practical criteria. (2) The results of the learner response test obtained an average score of 5 and the drawing effectiveness test of 5 average score value of very effective criteria, thus in terms of the attractiveness of learning media drawing augmented realitybased henna design ornaments is very interesting to use in learning.